NILAI BUDAYA DALAM PERIBAHASA KEI TENTANG PENGELOLAAN WILAYAH PESISIR - Akihary, Wilma (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
The cultural values that are covered in the way of life is manifested in men’s activities. The cultural values themselves are symbolized through the proverbs. As the expression, the proverb is basically the principle guideline of behavior. Within the proverb is contained a profound experience of the world view as well as the life wisdom that is tightly integrated to the society to which the language belongs. The proverb - known as misil-masal, liat daliat and sukat sarang - is still well recorded and used by Kei community as Kei language speaker. The people who live in the coastal area especially at the Kei Besar Island are generally the fishermen and farmers. However, in this research it will focus on the Kei Besar people’s view in managing their coastal area through the proverbs they use. The uses of words as the expression is closely related to the sea and their way of life especially in connected with fish and boat. The proverbs which are used by the people in Kei is the summary of their way of thinking about the values of life. The cultural values in these proverbs are firmness, strength, simplicity, mutual assistance, respect for the elders and leaders, wisdom, thinking before doing, and obedience.Keywords: Nilai Budaya, Peribahasa, Wilayah Pesisir